Effect of Obesity in Memory and Cognition (Global Journal of Medical Research, 2022)
Presently a day s obesity is one of the significant public issues all through the world among kids teenagers just as in grown-ups and old people From the distinctive animal models and clinical trials it was accounted that natural adequacy related to weight is connected with more regrettable memory function Evidence recognizes obesity as a significant danger factor for the beginning and progression of a few neurological problems associated with metabolic dysfunction and inflammation which are related to obesity are owing to consequences for the primarily cognitive impairment Numerous studies suggest that obesity results in neurological diseases such as Parkinson s disease and Alzheimer s disease which could be initiated by various metabolic changes related to CNS damage as well as cognitive loss or cognitive dysfunction Thus the purpose of this review was to evaluate the totality of research examining whether obesity is associated with cognitive function or cognitive decline and confounds the relationship between obesity and cognitive loss A review approach was employed using PubMed Google Scholar databases Worse memory function may directly be related to obesity with underlying mechanisms discussed here However it is uncertain whether adiposity itself is influencing cognitive changes and it drives the obesity-cognitive relationship
Keywords: obesity; alzheimer’s disease; parkinson’s disease; cognitive impairments